Development of Ecobrick Application – Based Android as an Innovative Media in Environmental Pollution Learning - Bibin Rubini; Hepi Hapipah; Anna Permanasari (Universitas Labuhanbatu, 2024)
Environmental pollution learning really needs technology-based media to increase the meaningful learning. Research has been conducted to develop an Android-based application as a media in the context of ecobrick to increase students' awareness to the environment conservation and student’s creativity. On using R and D with ADDIE design, the research was conducted through the steps: need analysis, designing, development, implementation, and evaluation. Research was then followed up with feasibility measurement To ensure that the media can be used in the learning practice. The validation was carried out through the expert and user (tearcher) validation test. In addition, survey techniques are used to explore direct responses by interviewing teachers. The validated media was then applied in the learning to measure the student awareness to the environment conservation. The research revealed that the media was very feasible to use with a high visibility index (expert validation index was 96.6%, meanwhile the CVR and CVI indexes were 0.98 and 0.99). The results of media implementation in environmental pollution learning show that the level of environmental awareness of students is in the high category (average student score = 82.49%), meanwhile the student’s creativity shows in the very good category (average student’s score was 92.97%)